2019
DOI: 10.1039/c8fo02327a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with yeast glycoprotein on growth performance, intestinal mucosal morphology, immune response and colonic microbiota in weaned piglets

Abstract: Antibiotics are commonly provided to weaned piglets; however, this practice has become controversial due to the increased occurrences of microbial resistance, and alternatives are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 46 publications
2
35
0
1
Order By: Relevance
“…It has reported that weaning stress could cause intestinal injury with the reduced intestinal villi height, the deepened recess, the changes of intestinal morphology from dense and finger-like villi to smooth and tongue-like villi, and the reduced active absorption capacity of the small intestine [5]. Normal intestinal function depends on the local barrier, which prevents the translocation of bacteria and endotoxins contained within the intestinal lumen to extraintestinal sites, and largely prevents the occurrence of diarrhea [34]. Intestinal mucosa permeability is the principal basis for the diagnosis of the intestinal barrier dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has reported that weaning stress could cause intestinal injury with the reduced intestinal villi height, the deepened recess, the changes of intestinal morphology from dense and finger-like villi to smooth and tongue-like villi, and the reduced active absorption capacity of the small intestine [5]. Normal intestinal function depends on the local barrier, which prevents the translocation of bacteria and endotoxins contained within the intestinal lumen to extraintestinal sites, and largely prevents the occurrence of diarrhea [34]. Intestinal mucosa permeability is the principal basis for the diagnosis of the intestinal barrier dysfunction [34].…”
Section: Discussionmentioning
confidence: 99%
“…Normal intestinal function depends on the local barrier, which prevents the translocation of bacteria and endotoxins contained within the intestinal lumen to extraintestinal sites, and largely prevents the occurrence of diarrhea [34]. Intestinal mucosa permeability is the principal basis for the diagnosis of the intestinal barrier dysfunction [34]. Serum D-lactate and DAO can be used as indicators of intestinal integrity of the gastrointestinal tract [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood samples were collected from the jugular vein into two tubes (heparinized tubes and non-heparinized tubes) from fasted piglets at the end of the trial [13]. The blood samples were then centrifuged at 3000 g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Os efeitos da suplementação alimentar com glicoproteína de levedura (800 mg/kg da ração), foram avaliados no desempenho e resposta imune a nível de microbiota intestinal na dieta de 240 leitões desmamados em média com 23 dias. Os animais alimentados com a glicoproteína de levedura apresentaram maior peso corporal final, aumento no ganho médio diário de peso e melhor conversão alimentar, além de proporcionarem melhor desenvolvimento intestinal, melhorando a saúde de leitões desmamados (Qin, et al, 2019).…”
Section: Levedurasunclassified